ANALISIS PENGARUH PEMASARAN DIGITAL MARKETING TERHADAP BRAND AWARENESS DI JEMBER STUDI KASUS RICH VILLAGE - Majestika, Rr Aurel Nalini; Hermawan, Haris; Izzudin, Ahmad (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The development of the current era makes people carry out economic activities through digital media, so that the growth of internet users is increasing by around 33%. This encourages the importance of the role of marketing in influencing people's preferences in choosing a product, which means it plays an important role in creating people who have awareness of a particular brand (brand awareness) so that the more recognized it will have a positive influence on the brand. Rich Village Jember is a fairly good housing in utilizing digital marketing. The purpose of this research is to find out and analyze context, communication, collaboration and connection that have a significant effect on brand awareness in Rich village Jember. This type of research is causality research. The population in this study are 85 families who occupy the Rich Village Jember housing. The sample used was saturated sampling technique so that the number of samples was 85 respondents. The analysis tool uses multiple linear regression. The results of the study prove that context, communication, collaboration and connection have a significant effect on brand awareness in Rich Village Jember.